2008
DOI: 10.1056/nejmoa0707865
|View full text |Cite
|
Sign up to set email alerts
|

Association of Systemic Lupus Erythematosus withC8orf13–BLKandITGAM–ITGAX

Abstract: We identified and then confirmed through replication two new genetic loci for SLE: a promoter-region allele associated with reduced expression of BLK and increased expression of C8orf13 and variants in the ITGAM-ITGAX region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
583
3
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 822 publications
(610 citation statements)
references
References 47 publications
16
583
3
1
Order By: Relevance
“…The haplotype marked by rs7574865 was found to be present on 31% of chromosomes of SLE patients but only on 22% of those in controls (odds ratio (OR) ¼ 1.55, P ¼ 1.87 Â 10 À9 ). 5 This association was replicated by Hom et al 7 with 341 added cases and 2905 added controls from the study of Remmers et al Association of STAT4 with SLE was also confirmed in several other studies. [8][9][10] SNP rs7574865 was found to be associated with lupus nephritis, ds-DNA antibody production and age of onset.…”
Section: Introductionmentioning
confidence: 68%
See 4 more Smart Citations
“…The haplotype marked by rs7574865 was found to be present on 31% of chromosomes of SLE patients but only on 22% of those in controls (odds ratio (OR) ¼ 1.55, P ¼ 1.87 Â 10 À9 ). 5 This association was replicated by Hom et al 7 with 341 added cases and 2905 added controls from the study of Remmers et al Association of STAT4 with SLE was also confirmed in several other studies. [8][9][10] SNP rs7574865 was found to be associated with lupus nephritis, ds-DNA antibody production and age of onset.…”
Section: Introductionmentioning
confidence: 68%
“…The two SNPs have moderate LD to each other, with r 2 equals 0.39 and 0.57 in Caucasians and Chinese, respectively. The strong association of rs13277113 in BLK with SLE in Chinese is not surprising, as the study by Hom et al 7 has shown that this SNP is associated with BLK expression in both Asians (Chinese and Japanese) and Caucasians. Stratification on subphenotypes on this gene did not show any significant differences (data not shown).…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations